THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ACADEMIC ACHIEVEMENT OF MIDWIFERY STUDENTS IN STIKES MEDIKA CIKARANG, INDONESIA - Ajeng Hayuning Tiyas; Dian Pratiwi; Istichana Zuliyati (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Educational success can be evaluated or viewed from students’ academic achievement. Academic achievement is influenced by several factors, such as intelligence and emotional intelligence. Intelligence only contributes roughly 20% of the success, while emotional intelligence may influence the other 80%. Emotional intelligence comprised of 5 indicators including self-awareness, self-control, self-motivation, empathy, and social skill.Low emotional intelligence leads to undesirable student academic achievement. Aims: This study aimed to determine the relation between emotional intelligence and academic achievement among DIII Midwifery Programme’s student at third grade in College of Health Science Medika Cikarang 2014. Methods: This research is a quantitative analytical research with cross sectional approach. A total of 83 students from DIII Midwifery Programme at third grade were selected randomly and be involved as participants. A questionnaire covered students’ Grade Point Average (GPA) and their emotional intelligence scale was employed. The data was then analysed by statistical Chi-Square test. Results: The result of the study indicates that there is a significant relation between emotional intelligence and academic achievement. Students who have high emotional intelligence tend to obtain higher academic achievement then students who have low emotional intelligence. Conclusion: The findings of the study is carrying an expectation to an improvement in academic programme planning, materials or other activities to be designed as the consideration to emotional intelligence development in order to optimize academic achievement’s students.